Process of mercury accumulation in urban strip river artificial wetland ecosystems: a case study of Changchun, a typical industrial city in Northeast China - Zong, Jing; Zhang, Hongjie; Li, Xuemei; Bai, Xinyu; Hu, Yufei; Cui, Dan; Wang, Zhaojun; Zhang, Gang (Frontiers in Plant Science, 2024)
Wetland ecosystems, as active mercury reservoirs, have become the most important sources and sinks of heavy metal mercury. Different from natural wetlands, artificial wetlands located in the urban section of rivers face problems such as diverse urban pollution sources and complex spatial and temporal changes. Therefore, in this study, five intermittently distributed artificial wetlands were selected from the upstream to the downstream of the Changchun section of the Yitong River, a tributary of the Songhua River basin in the old industrial base of Northeast China. The mercury levels in the water bodies, sediments and plants of the artificial wetlands were collected and tested in four quarters from April 2023 to analyze the spatial and temporal distribution characteristics of total mercury. The results showed that: in terms of spatial distribution, the distribution of mercury levels in the artificial wetland showed a gradual decrease from the upstream to the midstream, and then after reaching the midstream, the concentration increased to the downstream due to the remittance of external pollution sources and then decreased again; in terms of temporal distribution, the concentration of mercury in the water body and plants showed that it was higher than the other three seasons in spring, and that the concentration of mercury in the sediments was higher than the other three seasons in winter. Among the bioconcentration factors, the BCF of plants in the Beihai Wetland and the Bayhood Wetland were both greater than 1 in the spring; moreover, there was a strong correlation between the level of Hg content in plants and the ratio of Hg concentration in the water body and sediments in the spring (R² =0.862), which indicated that there was a stronger enrichment capacity for Hg in the early stage of plant growth, and the Hg contamination of the wetland could be mitigated to a certain extent. Overall, the total mercury output from the downstream watershed of the wetland ecosystem showed a decreasing trend. This may be due to the retention of particulate matter by aquatic plants in the artificial wetland and the deposition effect caused by regular salvage of dead aquatic plants.